MWCNTs Alleviated saline-alkali stress by optimizing photosynthesis and sucrose metabolism in rice seedling - Zhenhua Xu; Haiying Liu; Yanmin Yu; Dawei Gao; Chunxu Leng; Shuli Zhang; Ping Yan (Plant Signaling & Behavior, 2023)
Saline and alkali stress affects the growth and development, survival rate, and final yield of rice, while new nano materials can have a positive effect on rice growth. In order to investing the effects of carboxymethyl multi walled carbon nanotubes (MWCNTs) on the growth and development of rice seedlings under salt alkali stress, rice seedlings were cultured using rice variety “Songjing 3” using nutrient solution water culture method. The effects of MWCNTs on water absorption capacity, leaf photosynthesis, and sucrose metabolism of rice seedlings under 50 mmol/L saline-alkali stress (1NaCl: 9Na2SO4: 9NaHCO3: 1Na2CO3) conditions were investigated. The results showed that MWCNTs can improve the water use ability of roots and leaves, especially the water absorption ability of roots, which provides a guarantee for the improvement of rice biomass and the enhancement of leaf photosynthetic capacity under adverse conditions. After treatment with MWCNTs, the photosynthetic rate (Pn), stomatal conductance (gs), and transpiration rate (Tr) of leaves increased significantly, and the photochemical quenching value (qP), photochemical quantum efficiency value (Fv/Fm), and electron transfer rate value (ETR) of chlorophyll fluorescence parameters increased significantly, which is beneficial to the improvement of the PSII photosynthetic system. MWCNTs treatment promoted the increase of photosynthetic pigment content in leaves under salt and alkali stress, improved the ratio of Chla and Chlb parameters, increased the activities of key photosynthetic enzymes (RUBPCase and PEPCase) in leaves, increased the value of total lutein cycle pool (VAZ), and significantly enhanced the deepoxidation effect of lutein cycle (DEPS), which can effectively alleviate the stomatal and non stomatal constraints on leaf photosynthesis caused by salt and alkali stress. MWCNTs treatment significantly enhanced the activities of sucrose phosphate synthase (SPS) and sucrose synthase (SS) under salt and alkali stress, and decreased the activities of soluble acid invertase (SAInv) and alkaline/neutral invertase (A/N-Inv), indicating that MWCNTs promoted sucrose synthesis while inhibiting sucrose decomposition, thereby promoting sucrose accumulation in rice leaves. This study can provide theoretical and experimental basis for the application of MWCNTs to the production of rice under salt and alkali stress, and can find a new way for rice production in saline and alkaline lands.